사회복지시설 클라이언트의 폭력에 대한 종사자의 반응이 직무소진에 미치는 영향 - 시설의 대응체계와 인구통계적 특성의 조절효과를 중심으로 - 정은미; 박희서; Jung, Eun-Mee; Park, Hwie-Seo (韓國컴퓨터情報學會論文誌, 2011)
The purpose of this study is to suggest the policy implications through the analysis on the effects of social workers' negative reactions for client violence on burnout. Especially, This study is focused on identifying the moderating effects of demographic characteristics and institutional confrontations system. This study was carried out based on survey of social workers on social welfare facilities located in G metropolitan city and J province. The major findings can be summarized as follows. First, Social workers' negative reactions toward client violence affect on burnout significantly. Second, demographic characteristics and institutional confrontations system moderate the relationship between social workers' negative reactions toward client violence and their burnout. This study suggested some implications basing on the analytical results. 이 연구는 사회복지시설에서 클라이언트 폭력에 따른 시설종사자의 부정적 반응이 직무소진에 미치는 영향을 실증적으로 분석해 봄으로써 정책적 이론적 시사점을 도출한 연구이다. 특히 선행연구에서 매우 미흡하였던 인구통계적 변수와 시설 대응체계의 조절효과를 분석해 봄으로써 사회복지시설 종사자의 직무소진관리를 위한 시사점을 제시하는데 연구목적을 두었다. 이러한 연구목적을 달성하기 위해 G광역시와 J도에 소재하고 있는 사회복지시설 종사자들을 대상으로 표본추출하여 설문조사를 실시하였다. 이 연구의 분석결과 다음과 같은 시사점이 도출되었다. 첫째, 사회복지시설 종사자의 직무소진을 줄이기 위해서는 클라이언트 폭력에 대한 부정적 반응을 줄여야 하는 것으로 나타났다. 둘째, 클라이언트 폭력에 따른 종사자의 부정적 반응이 직무소진에 미치는 영향은 인구통계적 특성과 시설의 대응체계에 따라 다른 것으로 나타났다. 이 연구는 이러한 분석결과를 토대로 정책적 시사점을 제시하였다.